Preliminary assessment of the bird species composition and feeding guilds in forest plantation and natural forest areas, Kinarut, Sabah Malaysia - Andy R. Mojiol; Emilda Markus; Sharon Shen; Lim, Wing-Shen; Micheal Fisher (University of Technology Sarawak, 2025)
As one of the most noticeable inhabitants of vulnerable places, birds play a crucial part in the maintenance of the well-being of a forest ecosystem. The aforementioned causes related to land use change are putting pressure on the forest habitats, thus putting the local birds at risks of extinction. The purpose of this research was to examine the species compositions and identify the feeding guilds of birds presented in a natural forest (Kawang Forest Reserve) and a plantation forest (Kinarut Eco Forest Park) in Sabah, Malaysia. Mist-Net and Point-Count sampling techniques were applied in this study, to analyse the distributions of feeding guilds of birds in these radically different habitat types. A total of 15 species and 11 species of birds were captured by mist-nets in the natural forest and plantation forest respectively. The Pcynonotidae was the most common bird family detected at both study sites. The Carnivore, Carnivoreinsectivore, Insectivore, Insectivore-Frugivore, Frugivore, and Nectarivore were the six registered feeding guilds, where the Insectivore-Frugivores and insectivores were the most prevalent guilds for birds presented in both habitat types. The Shannon-Wiener Diversity Index analysis of species diversity revealed that the difference was not significant between the two study sites, although the bird diversity was generally lower in the plantation forest (H’=2.78) than in the natural forest (H'=3.08). The estimated bird population densities (D) in the plantation forest and natural forest were 427 individuals per hectare (CV=21.6%) and 100 individuals per hectare (CV=30.1%) respectively. The variability in species composition and density of bird between the two habitat types may be caused by the variability in the microclimate, distribution, and forest structure. This research provides the initial attempt in understanding the role of habitats or land cover types, guild types and human interferences in shaping the density, abundance and diversity of bird, which also represent the well-being of a forest ecosystem. Such a knowledge is vital in providing the necessary information for implementing sustainable management practices.